Evil bones [compact disc, unabridged] - Reichs, Kathy (Reichs, Kathy. Temperance Brennan series., 2025)
Small creatures - a rat, a rabbit, a squirrel - have been turning up throughout Charlotte, North Carolina, mutilated and displayed in the same bizarre manner. But one day, as Tempe is relaxing at home alongside her aimless, moody great-niece Tory, she's diverted by a disturbing call. Now, it seems, the perp is upping the ante. This find is larger. Could the remains be human?